2021
DOI: 10.3389/fbioe.2021.643722
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Surface Properties, Bacterial Motility, and Hydrodynamic Conditions on Bacterial Surface Sensing and Their Initial Adhesion

Abstract: Biofilms are structured microbial communities attached to surfaces, which play a significant role in the persistence of biofoulings in both medical and industrial settings. Bacteria in biofilms are mostly embedded in a complex matrix comprised of extracellular polymeric substances that provide mechanical stability and protection against environmental adversities. Once the biofilm is matured, it becomes extremely difficult to kill bacteria or mechanically remove biofilms from solid surfaces. Therefore, interrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
266
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(349 citation statements)
references
References 175 publications
5
266
6
2
Order By: Relevance
“…These results suggested that biofilm structure is not only dependent on the surface but also on the cyanobacterial isolate, as previously shown by Zheng et al [33].…”
Section: Structure Analysis Of Biofilms Developed On Tested Surfacessupporting
confidence: 87%
See 1 more Smart Citation
“…These results suggested that biofilm structure is not only dependent on the surface but also on the cyanobacterial isolate, as previously shown by Zheng et al [33].…”
Section: Structure Analysis Of Biofilms Developed On Tested Surfacessupporting
confidence: 87%
“…Since it is known that surface properties influence cell adhesion and subsequent biofilm formation [33,34], surface materials were first analyzed regarding their hydrophobicity, topography, and roughness. Table 1 presents the contact angles, hydrophobicity, and roughness values for the tested materials.…”
Section: Surface Characterization Of Materials and Cyanobacterial Isolatesmentioning
confidence: 99%
“…Bacterial adhesion to a surface is a multifactorial process [ 2 ], which is affected by various factors such as duration of the bacterial exposure to surfaces, bacterial characteristics (cell wall components, appendages, and motility), nutrients, and bacterial density [ 52 ]. The cell-cell bond between two genetically distinct microorganisms is known as coaggregation, and cohesion when a cell is attached to the surface [ 24 ].…”
Section: How Does the Process Of Surface Adhesion Occur?mentioning
confidence: 99%
“…The process of adhering to a surface involves the three types of interactions (specific, nonspecific, and mechanosensing), and happens with the formation of the conditioning film, which is the base on which biofilm grows, formed by organic and inorganic particles [ 22 , 52 ]. The particles present in the fluid that bathes the surface can settle and form a part of this conditioning film.…”
Section: How Does the Process Of Surface Adhesion Occur?mentioning
confidence: 99%
“…Such brushes can control the surface-bacteria interactions and thus, can discourage the bacterial adhesion ( Figure 4 c) [ 139 ]. More details on polymers with antiadhesive properties and on strategies to prevent bacterial adhesion can be further consulted in the literature [ 37 , 38 , 78 , 79 , 80 , 86 , 87 , 88 , 89 , 141 ].…”
Section: Recent Antimicrobial Structures Assembled From Polymers On Surfacesmentioning
confidence: 99%